Shear wave elastography combined with electromyography to assess the effect of botulinum toxin on spastic dystonia following stroke: A pilot study - Campanella, William; Corazza, Angelo; Puce, Luca; Privitera, Laura; Pedrini, Riccardo; Mori, Laura; Boccuni, Leonardo; Turtulici, Giovanni; Trompetto, Carlo; Marinelli, Lucio (Frontiers in Neurology, 2022)
Background: Shear wave elastography (SWE) is a method for carrying out a quantitative assessment of the mechanical properties of soft tissues in terms of stiffness. In stroke survivors, the paretic muscles may develop hypertonia due to both neural-mediated mechanisms and structural alterations with consequent muscular fibrous-fatty remodelling. Methods: Fourteen adult patients with spastic dystonia following stroke were recruited. Muscle hypertonia was assessed using the modified Ashworth scale (MAS). Muscle activation was measured by surface electromyography (sEMG) with the selected muscle in shortened (spastic dystonia) and stretched (dynamic stretch reflex) positions. SWE was performed on a selected paretic muscle and on the contralateral non-paretic one to calculate shear wave velocities (SWV) along and across muscular fibres. The modified Heckmatt scale (MHS) pattern was also determined. All evaluations were performed shortly before BoNT-A injections (T0) and one month later (T1). Results: All SWV on paretic muscles were higher than contralateral non-paretic ones (p<0.01). After BoNT-A injection, a significant reduction in MAS (p=0.0018), spastic dystonia (p=0.0043), and longitudinal SWE measurements, both in shortened (p=0.001) and in stretched muscular conditions (p=0.0029), was observed. No significant changes in SWV on non-paretic muscles were observed. Higher SWV resulted along the direction of muscular fibres versus across them (p=0.001). No changes resulted from the MHS evaluations after BoNT-A. There was a positive correlation between MHS scores and SWV values while the muscle was in the shortened position, but not with spastic dystonia recorded by sEMG. Conclusions: This is the first study evaluating the effect of BoNT-A on muscle hypertonia following stroke, assessed by both SWE and sEMG. These findings support SWE as a useful method to disclose intrinsic muscular remodelling, independently of the effect of spastic dystonia, in particular, while muscles were assessed in a neutral position. SWE measurements of muscle stiffness cannot tell apart neural-mediated and intrinsic muscle hypertonia. Interestingly, when sEMG activity is very limited, as in spastic muscles kept in a shortened position, SWE can provide a measurement of stiffness due almost completely to intrinsic muscle changes. Alongside sEMG, SWE could aid clinicians in the assessment of responses to treatments.